2016
DOI: 10.1364/boe.7.000688
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative optical coherence elastography based on fiber-optic probe for in situ measurement of tissue mechanical properties

Abstract: Abstract:We developed a miniature quantitative optical coherence elastography (qOCE) instrument with an integrated Fabry-Perot force sensor, for in situ elasticity measurement of biological tissue. The technique has great potential for biomechanics modeling and clinical diagnosis. We designed the fiber-optic qOCE probe that was used to exert a compressive force to deform tissue at the tip of the probe. Using the space-division multiplexed optical coherence tomography (OCT) signal detected by a spectral domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…In our previous work, we demonstrated a miniature quantitative OCE (qOCE) instrument which simultaneously measured the force exerted to tissue and the resultant tissue deformation [19]. We also demonstrated that our qOCE technique was able to provide depth resolved stiffness assessment in a muti-layer structure [20].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…In our previous work, we demonstrated a miniature quantitative OCE (qOCE) instrument which simultaneously measured the force exerted to tissue and the resultant tissue deformation [19]. We also demonstrated that our qOCE technique was able to provide depth resolved stiffness assessment in a muti-layer structure [20].…”
Section: Introductionmentioning
confidence: 94%
“…1(a)) utilizes a spectral domain OCT (SD OCT) engine operated at 1300nm. A detailed description of the system can be found in our previous publication [19,21]. Briefly, the system has a 91 kHz Ascan rate and a ~7.5μm axial resolution.…”
Section: Qoce Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent OCE works obtained micro-scale resolution [21][22][23][24] elastograms, improving the OCT signal processing to extract more accurate strain measurements and reducing the contact area to apply a more localized mechanical stimulus; e®ort in miniaturization resulted in the needle-based OCE for in vivo and in situ characterization. [25][26][27] Over the last few years, our group has pioneered a new indentation technique that has been tailored for applications in life science research. [28][29][30] The technique relies on a ferrule-top probe, which is obtained by assembling a millimeter-size cantilever, equipped with a % 100 m diameter sphere on its free hanging end on a small glass block.…”
Section: Introductionmentioning
confidence: 99%